Methodological support for forensic science in the USA and Ukraine: A comparative study - Nataliia Martynenko (Forensic Science International: Synergy)
The significant potential of proper methodological support in solving key tasks of forensic expert activity is noted. The procedure for certification and state registration of forensic examination methods introduced in Ukraine is analyzed. The composition and procedure for the activities of the advisory bodies of the Ministry of Justice of Ukraine which determine the relevance and priority of forensic examination research are investigated. The author identifies the areas of concern in the methodological support of forensic institutions, the addressing of which relates to the activities of the State in terms of legal support of forensics at the legislative and departmental regulatory levels.The requirements to the registration of research results by grantees of the US National Institute of Justice are clarified. The article compares research costs, access to scientific results, and promising research topics in the field of forensic science in the United States and Ukraine. Certain ways of solving the identified problems related to the methodological support of forensic expert activity were proposed, taking into account the specifics of the legal system of Ukraine and the experience of the National Institute of Justice in the United States. The author emphasizes the need for further development and strengthening of cooperation between forensic institutions and international organizations in the field of standardization.